Pengaruh Social Media Marketing Dan Store Atmosphere Terhadap Keputusan Pembelian Pada Kedai Kopi Halaman Belakang Di Cihuni Kabupaten Tangerang - Tri Widiastuti; Ivantan Ivantan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to examine the effect of Social Media Marketing and Store Atmosphere on Purchase Decision at Kedai Kopi Halaman Belakang. This research employs a quantitative descriptive method with an associative approach. The sampling technique used is probability sampling, with the sample size determined using the Rao Purba formula. The data analysis techniques include instrument testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing (t-test and F-test). The results show that Social Media Marketing (X1) and Store Atmosphere (X2) have a significant effect on Purchase Decision (Y), as indicated by the multiple linear regression equation Y = 1.143 + 0.302X1 + 0.741X2 + α. The coefficient of determination simultaneously is 90.5%, while the remaining 9.5% is influenced by other variables not examined in this study. Based on the partial hypothesis testing, Social Media Marketing (X1) has a t-value greater than the t-table (19.770 > 1.986) with a significance level of 0.000 < 0.05, indicating that H₀ is rejected and H₁ is accepted. This result demonstrates that Social Media Marketing has a positive and significant effect on Purchase Decision. Furthermore, Store Atmosphere (X2) has a t-value greater than the t-table (27.061 > 1.986) with a significance level of 0.000 < 0.05, indicating that H₀ is rejected and H₂ is accepted, meaning that Store Atmosphere has a positive and significant effect on Purchase Decision. The simultaneous hypothesis testing shows that the F-value is greater than the F-table (444.122 > 3.09) with a significance value of 0.000 < 0.05, indicating that H₀ is rejected and H₃ is accepted. Therefore, it can be concluded that Social Media Marketing and Store Atmosphere simultaneously have a positive and significant effect on Purchase Decision at Kedai Kopi Halaman Belakang